Fator de reprodução de Meloidogyne graminicola em cultivares de arroz irrigado e quantificação de dano - Aita, Natalia Tobin (2019)
The gall-forming nematodes belonging to the genus Meloidogyne are one of the major damage-causing parasites in agricultural crops, with a major impact on world cereal production. For irrigated rice culture, Meloidogyne graminicola is the most frequent species due its adaptation, survival and multiplication in areas under flood management. In Rio Grande do Sul state, which is responsible for 70% of national rice production, surveys have been carried out to identify areas infested by Meloidogyne graminicola. Once areas were identified with parasite presence, the need of studies to better understand how it impact rice production in the state appear. The present study evaluated the reaction of different rice irrigated cultivars to M. graminicola inoculation and quantified the damage caused by the pathogen in different population densities. Two experiments were performed under greenhouse conditions and a third trial was carried on field. The first experiment was carried to evaluate the reaction test of six rice cultivars after M. Graminicola inoculation. At 60 days after inoculation (DAI) roots and substrate were extracted to determine reproduction factor. The second experiment deal with the interaction with two cultivars GURI INTA CL and IRGA 424 RI, which have different reaction to Meloidogyne graminicola. In the second experiment cultivars were inoculated with seven different inoculums densities and it was evaluated at 60 DAI for stature, fresh shoot mass, fresh root mass and number of juveniles and eggs in root tissue and substrate. A third trial was installed at the field in order to quantify productivity damage under three different ranges of population densities of M. graminicola. GURI INTA CL and PUITÁ cultivars presented highest reproductive factors, IRGA 428 and SCS 116 cultivars showed intermediate values and IRGA 424 IR and SCS 121 cultivars presented lowest reproductive factors. The GURI INTA CL and IRGA 424 RI cultivars presented changes in the evaluated parameters, mainly the decrease of the mass of the root system, which responded linearly as the inoculated densities increased. It was observed a reduction in productivity as the nematode population increased.